Isolation and Characterization of a heavy metal-tolerant diesel oil - degrading strain (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2013)
A diesel-degrading bacterium has been isolated from a local university soil. The isolate was tentatively identified as Burkholderia sp. strain DRY27 based on the carbon utilization profiles using Biolog GN plates and partial 16S rDNA molecular phylogeny. Isolate 27 showed an increase cellular growth with respect to diesel concentrations from 0% until 3% where the optimum growth occurring at 3% (v/v) diesel concentration. Based on the optimization studies, sodium nitrate proved to be the best nitrogen source. Sodium nitrate was optimum at 7.7 gl-1 .The optimal temperature and optimal pH for this bacterium was between 10 to 40 oC and pH 7.5 to pH 8.5 respectively. Diesel components was proven to be completely removed from the reduction in the hydrocarbon peaks monitored by Solid Phase Microextraction Gas Chromatography analysis. These prove that this bacterium is the right bacterium for bioremediation of diesel spills and pollution in the tropics.
Keywords: Diesel-degrading; Burkholderia sp.; Isolation; Characterization